PERBANDINGAN TINGKAT KONSENTRASI BELAJAR ANAK SEKOLAH DASAR DILIHAT DARI KEBIASAAN MAKAN PAGI - Rahmawati, Dewi Arifiani (BELIA: Early Childhood Education Papers, 2014)
Breakfast very important for children. Breakfast with the good menu can optime the brainâs work so that children wiil have well concentrate. This should be supported by physical condition and adequacy of energy. It is appropiate with the purposes of this study to determine differences level of learning concentration of elementary school students (first year of elementary school) seen from the habit of breakfast. This study uses quantitative research methods with study comparative research design. The research data retrieval using questionnaires completed by parents and students. This study population are 388 students, while the sample of this study are 162 students. The results showed that there are learning concentration level differences of children having breakfast and not. Based on the test of normality that has been done, it can be seen from the significant probability value that all normal variables as worth more than 5 % or 0.05. Breakfast habits variabel of first year Elementary School have significance 0.067 greater than 0.05. Whereas variable of learning concentration level of students has a significance value 0.20, which means greater than 0.05. While the results of homogeneity test showed significanace value 0.288. Results of analysis hypotheses using t-test to see the comparation between children learning concentration having breakfast and not showed significance valeu 0,297 > @ (0,05) so Ha is accepted. This means that there are differences in learning concentration levels between children having breakfast and not. It is recommended for students, parents, teachers and the general public in order to raise awareness of the importance of children having breakfast and its influences in the learning process can also indirectly affect student achievement.